Perubahan Distribusi Ukuran Partikel Tepung Iles-Iles Hasil Pengolahan dengan Metode Penggilingan Bertingkat - Sukrisno Widyotomo; Hadi K. Purwadaria; Atjeng M. Syarief; Sri Mulato (agriTECH, 2004)
The objectives of this research were to observe the distribution particle sizes change of konjac flour by dry milling method. The milling process of konjac flour included the milling by rotary cutter, burr mill, and conical ball mill. The particle size and the size distribution were determined by sieving, microscopic, and scanning electron microscope methods. The data obtained by using the microscopic method indicated the smallest geometric mean particles size, while data from the sieve method indicated the largest geometric mean size. The pictures obtained by using scanning electron microscope method showed the particles has broken after milling process by conical ball mill. The results indicated that the series of milling process decreased the geometric mean diameter, the finenes modulus, and the uniformity index of konjac flour particles.